The benefits and safety of oral sequential antibiotic therapy in non-complicated and complicated Staphylococcus aureus bacteremia. (January 2021) - Pérez-Rodríguez, M. Teresa; Sousa, Adrián; Moreno-Flores, Antonio; Longueira, Rebeca; Diéguez, Patricia; Suárez, Milagros; Lima, Olalla; Vasallo, Francisco J.; Álvarez-Fernández, Maximiliano; Crespo, Manuel
Highlights: Staphylococcus aureus bacteremia is associated with high morbidity and mortality. Its adequate management includes long-term intravenous therapy. Oral sequential therapy could be a safe option in selected patients. Abstract: Background: Treatment optimization for serious infections, such as Staphylococcus aureus bacteremia (SAB), is a challenge for antimicrobial stewardship teams. Currently, SAB guidelines recommend a completely intravenous therapy (CIT). Objectives: The objective of the study was to analyze the usefulness and safety of oral sequential therapy (OST) in SAB. Patients and methods: We conducted a retrospective, observational study in a tertiary teaching hospital in Spain. The inclusion criteria were complicated and non-complicated monomicrobial SAB and an adequate duration of therapy, with patients classified into OST or CIT. The primary endpoint was the 90-day recurrence of S. aureus infection. We also analyzed the mortality, the length of the hospital stay, and the duration of the intravenous antibiotic administration. Results: Of a total of 201 patients with SAB, 125 (62%) underwent OST. The most commonly administered oral antibiotic was trimethoprim-sulfamethoxazole (66% of patients). Of those administered OST, 43% had complicated bacteremia (most with an osteoarticular source of infection), and 6% had an intravascular device. The 90-day recurrence rate was 4%, with no differences between the two groups. The duration of the therapy (22 [16–28] vs. 13 days [8–17] for CIT and OST, respectively; p < 0.001) and the hospital stay (36 [27–71] vs. 18 days [13–29] for CIT and OST, respectively; p < 0.001) were shorter for OST. MRSA was related with mortality (OR 4.4, 95% CI [1.67−11.37]; p = 0.003). Conclusions: OST for properly selected patients with SAB could be a safe therapeutic option and can reduce their use of CIT and their hospital stay.